One Territory – One Bishop? Or, Shall the Syrian Rites Die? - Thonippara, Francis (Asian Horizons, 2011)
N.A. Thomas, One Territory – One Bishop? Or, Shall the Syrian Rites Die? Kottayam: Denha Services, 2011 (second edition; first published in 1971). Pages: 179. ISBN: 978-81-88456-62-8